Hallucinations in Bipolar Disorder: A Spectrum Between Psychotic Features and Affective Intensification - Pramesta, Linda Ramadhanty; Sakdyah, Halimatus; Egy Atthahirah Septina; Ikhsan, Muhammad; Shafira, Alsa; Winaryani; Algristian, Hafid (Indonesian Scientific Publication, 2025)
Hallucinations, while traditionally associated with schizophrenia spectrum disorders, are increasingly recognized in individuals with bipolar disorder, particularly in rapid cycling forms. Such manifestations complicate diagnosis and, if overlooked, may lead to poorer prognoses. This case report describes the clinical course and management of a 30-year-old female with bipolar I disorder, rapid cycling subtype (≥6 episodes/year), presenting with impulsivity, emotional instability, and mild auditory hallucinations. Her history included childhood emotional and physical abuse. Assessments involved DSM-5 structured interviews, the Young Mania Rating Scale (YMRS), Hamilton Depression Rating Scale (HAM-D), and Difficulties in Emotion Regulation Scale (DERS). Findings indicated pronounced affective lability, trauma-related personality traits overlapping with borderline personality disorder, and partial resistance to prior pharmacological treatment. During inpatient care, she was treated with valproate and low-dose quetiapine, complemented by psychoeducation and trauma-focused psychotherapy, producing notable improvement despite residual mood instability. This case underscores the interaction between trauma, affective dysregulation, and psychotic-like features in rapid cycling bipolar disorder (RCBD). Hallucinations here may reflect affective intensification rather than primary psychosis, stressing the need for careful differential diagnosis and trauma screening. The implications advocate routine trauma-informed assessments in bipolar disorder and highlight the efficacy of multimodal strategies combining pharmacological stabilization with targeted psychotherapy. Integrating trauma-focused care with mood management can enhance long-term outcomes in RCBD, particularly where conventional treatment shows partial resistance.